2016
DOI: 10.1111/jmft.12155
|View full text |Cite
|
Sign up to set email alerts
|

Life After Bariatric Surgery: Perceptions of Male Patients and Their Intimate Relationships

Abstract: This study explores the experiences of 20 men who have had bariatric surgery, focusing on their couple or marital relationships. The researcher concentrates on men's perspectives regarding relationship satisfaction, sexual intimacy, and social support after surgical intervention. Phenomenology and family systems theory were used to guide the study from which emerged three themes: (a) Unintended consequences (unpredicted problems occurring within intimate relationships); (b) Intimacy as bittersweet (experiencin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 83 publications
(83 reference statements)
2
23
0
2
Order By: Relevance
“…Remodelling family patterns is more difficult when there are substantial discrepancies within the family, with regard expectations and knowledge regarding the demands and implications that unexpected change has on interrelations and the management of day-to-day life. This is in accordance with earlier research on the individual level, which showed that unrealistic expectations and lack of support may negatively affect self-care management in the form of diet and physical activity, as well as the maintenance thereof (Moore & Cooper, 2015; Sharman et al, 2015). Families’ involvement and negative expression of support can be obstructive, depending on the relationship quality and conflict resolution abilities (Mayberry & Osborn, 2014; Rosland, Heisler, & Piette, 2012).…”
Section: Discussionsupporting
confidence: 92%
“…Remodelling family patterns is more difficult when there are substantial discrepancies within the family, with regard expectations and knowledge regarding the demands and implications that unexpected change has on interrelations and the management of day-to-day life. This is in accordance with earlier research on the individual level, which showed that unrealistic expectations and lack of support may negatively affect self-care management in the form of diet and physical activity, as well as the maintenance thereof (Moore & Cooper, 2015; Sharman et al, 2015). Families’ involvement and negative expression of support can be obstructive, depending on the relationship quality and conflict resolution abilities (Mayberry & Osborn, 2014; Rosland, Heisler, & Piette, 2012).…”
Section: Discussionsupporting
confidence: 92%
“…Other Individual Factors ‐ It is important to consider contextual factors such as obesity when working with bariatric clients as individuals or part of a couple or family system as it can impact intimate relationships (Moore & Cooper, ). ‐ Clinicians should assess for a variety of factors of aggression to better understand violence in relationships (Marshall & Holtzworth‐Munroe, ). ‐ Therapists need to consider their own biases when working with couples reporting childhood sexual abuse as a contributor to therapy effectiveness (Anderson & Miller, ). ‐ Clinicians should address women's body esteem with both partners to potentially increase marital satisfaction (Holt & Lyness, ). ‐ PTSD correlates with lower marital satisfaction, increased verbal aggression, and lower sexual satisfaction for individuals who were prisoners of war (Dekel & Solomon, ). ‐ Couples therapy can increase communication and problem solving in relationships where the woman is a survivor of childhood sexual abuse and currently in recovery (Trute, Docking, & Hiebert‐Murphy, ). ‐ Diary reports indicated that husband's depression levels mediated the amount of discussion of sexual intimacy, leading to greater use of angry expressions and depressive expressions by both husbands and wives (Papp, Goeke‐Morey, & Cummings, ). ‐ Compared to nonvictims, newlywed women with a history of childhood sexual abuse experience sexual re‐victimization in marriage, which may increase trauma symptoms (DiLillo et al., ). ‐ Body image issues are not a “female problem” only, positive body image is an important predictor of sexual satisfaction for both males and females (Holt & Lyness, ). ‐ Supportive partners may aid in a woman's recovery from a hysterectomy, however partners may lack information about how the surgery may impact the sexual relationship (Askew & Zam, ). …”
Section: Resultsmentioning
confidence: 99%
“…). Other scholarship has investigated the ways in which men's intimate and professional relationships are altered following bariatric surgery (Moore, Brooks, and King ; Moore and Cooper ).…”
Section: Why Men? Why Bariatric Surgery?mentioning
confidence: 99%
“…Overall, however, literature exploring men's lived experiences of surgically induced weight loss and dietary restriction management remains woefully lacking (for exceptions, see Groven, Galdas, and Solbrække ; Moore and Cooper ; Moore, Brooks, and King ; Natvik et al. ).…”
Section: Why Men? Why Bariatric Surgery?mentioning
confidence: 99%